Lipoprotein Levels in Early Adulthood and NAFLD in Midlife: The Coronary Artery Risk Development in Young Adults (CARDIA) Study - Sahil Khanna; John T. Wilkins; Hongyan Ning; Norrina B. Allen; Cora E. Lewis; J. Jeffrey Carr; Donald Lloyd-Jones; Lisa B. VanWagner (Journal of Nutrition and Metabolism)
Objective. We evaluated the association of apolipoprotein B (apoB) with low-density lipoprotein cholesterol (LDL-C), non-high-density lipoprotein cholesterol (non-HDL-C), and triglycerides (TG) in early adulthood with concordant/discordant associations and midlife NAFLD. Methods. Participants from the CARDIA study were included (n = 2,655; baseline mean age: 25.0, 59.1% female, and 48.6% black). NAFLD was defined as liver attenuation ≤40 Hounsfield units after excluding other causes of liver fat. Logistic regression models assessed the odds of Y25 NAFLD among tertiles of apoB, LDL-C, non-HDL-C, and TG and quartiles of the apoB/TG ratio. Discordance/concordance analyses examined the association of apoB with each lipid marker and Y25 NAFLD. Results. The Y25 NAFLD prevalence was 10%. The high-tertile TG group (OR 1.87, 95% CI, and 1.30–2.69) and the low- (OR 1.98, 95% CI, and 1.30–3.01) and middle-apoB/TG ratio groups (OR 1.78, 95% CI, and 1.17–2.72) had the greatest odds of midlife NAFLD. Using discordance/concordance analysis, the high-apoB/high-TG group had the highest odds of NAFLD (OR 1.69, 95% CI, and 1.09–2.61) followed by the low-apoB/high-TG group. The high apoB/low TG group had the lowest odds of NAFLD. Conclusions. Among the studied lipid markers in early adulthood, TG levels have the strongest and most consistent association with midlife NAFLD.